A long-cycling anode based on a coral-like Sn nanostructure with a binary binder. Issue 70 (14th August 2019) - Liu, Yuhang; Sun, Jinmeng; Du, Hongfang; He, Song; Xie, Linghai; Ai, Wei; Huang, Wei
Abstract : We report a facile one-pot displacement reaction for the synthesis of a 3D coral-like Sn nanostructure towards a long-cycling Li-ion battery anode. Abstract : A coral-like metallic Sn nanostructure was synthesized towards an advanced Li-ion battery anode via a facile one-pot displacement reaction. In the presence of 5 wt% sodium carboxymethyl cellulose and 5 wt% graphene oxide as a binary binder, the electrode demonstrates extraordinary Li storage behaviors in terms of high initial coulombic efficiency (68.7%), long-cycling life (800 cycles with a retention capacity of 422 mA h g −1 at 500 mA g −1 ), and superb rate capability. The fascinating electrochemical performance could be attributed to the 3D interconnected nanostructure together with the binary binder to ease the volume expansion of Sn.